The effect of background wind on mesoscale circulations above variable soil moisture in the Sahel. (20th September 2012) - Dixon, N. S.; Parker, D. J.; Taylor, C. M.; Garcia‐Carreras, L.; Harris, P. P.; Marsham, J. H.; Polcher, J.; Woolley, A.
Abstract Observational data are presented from several low‐level flights carried out during the afternoon over areas of the Sahel that had been previously wetted by rain. The measurements are used to quantify the response of boundary‐layer circulations to surface heterogeneity over a range of ambient conditions. Satellite observations of surface temperature anomalies show that soil moisture is significantly correlated with the surface heterogeneity in a majority of flights. By analysing the flight data in frequency space, consistently high levels of coherence are found between surface and flight‐level measurements at length‐scales around 25 km, indicating the presence of mesoscale circulations induced by the surface variability. The circulations are detectable in all of the nine flights where the mean sensible heat flux is high enough and they persist in a range of background wind speeds up to 5 m s−1. Further analysis confirms that the spatial phase‐difference between surface and flight‐level variables increases with the strength of the mean wind along the flight track. The boundary‐layer thermal anomalies and circulations are advected downstream by the mean wind, and lead to convergent uplift on the order of 0.25 m s−1 at the 25 km scale. These results compare well with those from a cloud‐resolving model and are broadly consistent with an analytical, linear model of a heated boundary layer. By demonstrating the significance of soil moisture in driving the circulations, the study shows that soil moisture is a likely cause of the negative precipitation feedback seen in recent remote sensing studies over the region. Copyright © 2012 Royal Meteorological Society